2-(Di-phenyl-methyl-idene)-2,3-di-hydro-1H-inden-1-one. - FRANKISH, NEIL (My University, 2013)
In the title mol-ecule, C22H16O, the indanone ring system is approximately planar with a dihedral angle between the fused rings of 5.13 (14)°. Two benzene rings are linked together at one side of a double bond, sitting on either side of the indanone ring system and making dihedral angles of 70.30 (12) and 44.74 (13)° with it. In the crystal, hydrogen bonding is not present, but weak C-H⋯π or π-π inter-actions occur and mol-ecules form a sheet-like structure in the bc plane.
PUBLISHED
Keywords: Pharmacy